Safety Management Model of Tourism City Municipalities in Eastern Economic Corridor - LEE-ANANT, Chayapoj (Journal of Environmental Management and Tourism, 2023)
This research was aimed to assess the level of concern and satisfaction level of safety, study safety management, and suggest a safety management model of Na Jomtien Subdistrict Municipality, Sattahip District, Chonburi Province, Thailand. A mixed method research was employed which was a combination of quantitative research and qualitative research by examining 400 samples and 30 significant participants. The research instruments consisted of a questionnaire about general information, safety concern level, safety satisfaction level, and a semi-structured interview about security management of Na Jomtien Municipality. Quantitative data were analyzed using mean, standard deviation, and analyzed the qualitative data using coding analysis. The results were that foreign tourists had a high level of security concern and a high level of safety satisfaction. In addition, it was found that Na Jomtien Municipality had a concrete safety management that was consistent with various policies and responded to the needs of the local people. The study revealed that the safety management model for the tourism city municipalities in Eastern Economic Corridor (EEC) should contain each of the following aspects, including 1) Crime, 2) Accident, 3) Natural disaster, 4) Prevention of disappearance/getting lost, 5) Travel, 6) Exploitation, 7) Health and hygiene and 8) Environment.